Effect of pH, Temperature and S02 Concentration on the Malo-Lactic Fermentation Abilities of Selected Bacteria and on Wine Colour - Van Der Westhuizen, Louisa M.; Loos, M.A. (South African Journal of Enology and Viticulture, 2017)
Thirty malo-Iactic bacterial cultures, isolated from red wines from 10 Western Cape wineries, were tested for their malo-Iactic fermentation abilities in Cinsaut wine. Each isolate was tested at S02 concentrations of 34 and 61 mg/C pH levels of 3,5 and 3,8, and temperatures of 15 and 20 °C. The wines were inoculated after alcoholic fermentation, and malo-Iactic fermentation was followed by paper chromatography tests for the following 5 months. At this point the colour of each oottle of wine which had undergone malo-Iactic fermentation, was determined and the colour loss calculated. The lower S02 concentration and higher temperature were significantly more favourable to malo-lactic fermentation. Two of the Leuconostoc oenos isolates completed malo-Iactic fermentation highly significantly more rapidly than nearly all other L. oenos, Lactobacillus and Pediodoccus isolates under the conditions tested. No great differences, few of which were significant, were found amongst the other isolates. The higher S02 concentration was the most important single factor causing colour loss in the experimental wines. The 30 bacterial cultures tested did not produce significantly different losses in colour.